2012
DOI: 10.1002/jbm.a.34321
|View full text |Cite
|
Sign up to set email alerts
|

High mineral affinity of polyphosphoester ionomer–phospholipid vesicles

Abstract: Bone-specific drug delivery is important for the treatment of osteoporosis and osseous metastases. However, there have been limitations in the design of drug carriers having bone affinity. We synthesized amphiphilic polyphosphoester ionomers (CH-PHE) and modified them to 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) vesicles. The ζ-potential of the vesicles was decreased by immobilization of CH-PHE; the amount was influenced by the structure and fraction of CH-PHE. The release rate of 5-carboxyfluorescein fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…For example, Xiong et al have reported that the degradation of polyphosphoesters is accelerated in the presence of alkaline phosphatase . Additionally, polyphosphoesters are found to show high binding affinity to bone tissues, thus considered to be candidates as fascinating biodegradable polymers possibly applied for hard tissue regenerations and drug delivery system. If we can utilize the polyphosphoesters as a degradable component of PRX, the potential bio­materials application of PRXs would be further expanded to novel biodegradable hydrogels and nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xiong et al have reported that the degradation of polyphosphoesters is accelerated in the presence of alkaline phosphatase . Additionally, polyphosphoesters are found to show high binding affinity to bone tissues, thus considered to be candidates as fascinating biodegradable polymers possibly applied for hard tissue regenerations and drug delivery system. If we can utilize the polyphosphoesters as a degradable component of PRX, the potential bio­materials application of PRXs would be further expanded to novel biodegradable hydrogels and nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol (CH) is a major candidate as an initiator in the preparation of amphiphilic PPDEs because alcohols can be employed for organocatalytic ROP of cyclic phosphate monomers. Amphiphilic P(EP x /EEP y ) [CH-P(EP x /EEP y )] that was composed of EP and EEP units was first synthesized and immobilized on 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) vesicles (Figure 5b), which resulted in the zeta-potential becoming more negative with increasing amounts of immobilized CH-P(EP x /EEP y ) [30]. The stability of the vesicles was then effectively improved by surface modification and was controlled by changing the fraction of DOPC and CH-P(EP x /EEP y ).…”
Section: Polyphosphodiesters (Ppdes) In Mineral-binding Nanoparticlesmentioning
confidence: 99%
“…Water‐soluble negatively charged polyphosphodiesters are also attractive polyelectrolyte materials. They can be achieved by selective hydrolysis of the pendant side chain which is a quite challenging reaction as the backbone integrity should be preserved. Interestingly, poly(phosphotriester) bearing allyl pendant groups can be easily converted into such polyelectrolyte by simple nucleophilic reaction, the allyl group playing the role of protecting group in this case (Scheme ).…”
Section: Broadening Functionalities Of Ppes By Post‐polymerization Rementioning
confidence: 99%